Mid-Term Effects of Conservative Soil Management and Fruit-Zone Early Leaf Removal Treatments on the Performance of Nerello Mascalese (Vitis vinifera L.) Grapes on Mount Etna (Southern Italy) - Elisabetta Nicolosi; Valeria Iovino; Gaetano Distefano; Mario Di Guardo; Stefano La Malfa; Alessandra Gentile; Alberto Palliotti; Giuseppina Las Casas; Filippo Ferlito (Agronomy, 2021)
The aim of this study was to analyze the mid-term influence of minimum tillage (MT) combined with early leaf removal (ELR) on the performance of the black grapevine variety Nerello Mascalese (Vitis vinifera L.). The research was carried out from 2015 to 2018 in a vineyard located in the Mount Etna area, East Sicily, Southern Italy. An average of about 8000 cm2 of leaves were removed from the ELR vines, corresponding to a canopy defoliation of 44% in 2017 and 30% in 2018. As for the stem water potential of both primary and lateral leaves, ELR-MT treatment showed the best performance (up to −0.4 MPa) among the four combinations. In 2017, no differences in yield/vine were found among treatments, whereas in 2018 the yield was significantly lower in ELR treatments. Among the different treatments performed, the ELR-MT showed the best results both in terms of physiological plant parameters (water status and photosynthetic activity) and fruit quality (higher concentration of sugars and total anthocyanins and polyphenols). ELR-MT treatment is also associated with a lower incidence of tillage operations from four to only one per year (−60–70 h/ha). In contrast to what was observed in the first 3 years of application (i.e., from 2015 to 2017), yield was heavily penalized during the fourth year of application (2018), probably due to the excessive depletion of nutritional reserves, the reduction of bud fertility and the unfavorable meteorological condition. For these reasons, the ELR-MT combination might require an interruption every 2–3 years of application.